Revitalization of Sundanese Language in Elementary Education Through Culinary Thematic Board Game Design - Fatmanto, Gricelda Khalilah; Nurhidayat, Martiyadi; Bahri, Nurul Fitriana (Jurnal Paedagogy, 2025)
This study aims to design learning media that can improve understanding of the Sundanese language, including traditional Sundanese cuisine, among children aged 9–12 years. This study employs a descriptive qualitative method, including observation instruments, interviews, documentation, and literature review. The data analysis technique utilizes comparative analysis with similar products. The findings of this study indicate that, based on the analysis of six design aspects (user, material, dimensions, visual, functional, and operational), Ngagigit Sunda is notably superior and has great potential for development as an educational learning tool to enhance motivation and understanding of the Sundanese language among children aged 9–12 years, compared to similar products that are purely entertainment-based without local educational content.